Tolkien the medievalist - Chance, Jane, 1945- (Routledge studies in medieval religion and culture, 2003)
Interdisciplinary in approach, this book provides a fresh perspective on J.R.R. Tolkien's medievalism. Fifteen essays explore how professor Tolkien responded to a modern age of crisis - historical, academic and personal.